Serum Level of IL-6, Reactive Oxygen Species and Cortisol in Patients with Recurrent Aphthous Stomatitis related Imbalance Nutrition Intake and Atopy - Nanan Nur'aeny; Dida Akhmad Gurnida; Oki Suwarsa; Irna Sufiawati (Institute for Research and Community Services (LPPM) ITB, 2020)
One of the most common oral ulcerations is recurrent aphthous stomatitis (RAS), affecting approximately 20% of the general population worldwide. The etiology of RAS is still unclear but it is considered to be multifactorial, including imbalanced nutrition intake and allergic conditions such as atopy. The purpose of this study was to investigate the differences and correlation between the serum level of IL-6, reactive oxygen species (ROS), and cortisol in RAS patients. Our study was cross-sectional and used a consecutive sampling method. There were significant differences of IL-6 and ROS levels in all groups (p = 0.000, p = 0.049 respectively) and a significant correlation between cortisol and ROS in the RAS group without atopy (r = -0.985, p = 0.015). Serum IL-6 and ROS measurement may be used for detecting RAS caused by malnutrition or atopy but not cortisol for patients without psychological stress detected. This is consistent with the results of a very strong correlation with a negative value between cortisol and ROS in RAS without atopy.